Literature and consciousness. An exploration from the cognitive sciences. Introduction - Gamoneda Lanza, Amelia; Cheguhem, Mauricio (Tropelías: Review of Literary Theory and Comparative Literature, 2022)
Introduction of the dossier on the study of the implications in Literature of notions and aspects of consciousness contributed from Cognitive Sciences
Keywords: consciousness; awareness; Literatura and Cognition; Cognitive Sciences; embodied cognition